PLK:Δgra9 Live Attenuated Strain Induces Protective Immunity Against Acute and Chronic Toxoplasmosis - Li, Jixu; Galon, Eloiza May; Guo, Huanping; Liu, Mingming; Li, Yongchang; Ji, Shengwei; Zafar, Iqra; Gao, Yang; Zheng, Weiqing; Adjou Moumouni, Paul Franck; Rizk, Mohamed Abdo; Tumwebaze, Maria Agnes; et al. (Frontiers in Microbiology, 2021)
Toxoplasmosis is a zoonotic parasitic disease caused by the obligate intracellular protozoa Toxoplasma gondii, which threatens a range of warm-blooded mammals including humans. To date, it remains a challenge to find safe and effective drug treatment or vaccine against toxoplasmosis. In this study, our results found that the development of a mutant strain based on gene disruption of dense granule protein 9 (gra9) in type II PLK strain decreased parasite replication in vivo, severely attenuated virulence in mice, and significantly reduced the formation of cysts in animals. Hence, we developed an immunization scheme to evaluate the protective immunity of the attenuated strain of Δgra9 in type II PLK parasite as a live attenuated vaccine against toxoplasmosis in the mouse model. Δgra9 vaccination-induced full immune responses characterized by significantly high levels of pro-inflammatory cytokine interferon gamma (IFN-γ) and interleukin-12 (IL-12), maintained the high T. gondii-specific IgG level, and mixed high IgG1/IgG2a levels. Their levels provided the complete protective immunity which is a combination of cellular and humoral immunity in mouse models against further infections of lethal doses of type I RH, type II PLK wild-type tachyzoites, or type II PLK cysts. Results showed that Δgra9 vaccination proved its immunogenicity and potency conferring 100% protection against acute and chronic T. gondii challenges. Together, Δgra9 vaccination provided safe and efficient immune protection against challenging parasites, suggesting that PLK:Δgra9 is a potentially promising live attenuated vaccine candidate.